2016
DOI: 10.1038/srep38944
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iron and boron combinations on the suppression of Fusarium wilt in banana

Abstract: The effects of mineral nutrient on banana wilt disease, which are the result of a competitive relationship between host plants and pathogens, can affect the interactions of plants with microorganisms. To investigate the mineral nutrient effect, hydroponic experiments were conducted in glasshouse containing combinations of low, medium, and high iron (Fe) and boron (B) concentrations, followed by pathogen inoculation. High Fe and B treatment significantly reduced the disease index and facilitated plants growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 41 publications
0
15
0
2
Order By: Relevance
“…Indeed, iron and other nutrients (e.g. Zn 2+ , Mn 2+ , Cu 2+ ) known as reductants in redox reactions have a deleterious effect on the establishment of Fusarium species in plants (Ruiz et al 2015;Dong et al 2016), while mycorrhizal fungi provide iron to plants (Adeleke et al 2012). Our current results indicate that iron availability is highly associated with the vulnerability of plant roots to necrotrophic pathogens.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Indeed, iron and other nutrients (e.g. Zn 2+ , Mn 2+ , Cu 2+ ) known as reductants in redox reactions have a deleterious effect on the establishment of Fusarium species in plants (Ruiz et al 2015;Dong et al 2016), while mycorrhizal fungi provide iron to plants (Adeleke et al 2012). Our current results indicate that iron availability is highly associated with the vulnerability of plant roots to necrotrophic pathogens.…”
Section: Discussionmentioning
confidence: 65%
“…Iron levels have been found to play an essential role in both fungal virulence and plant defense response (Dong et al 2016;Expert and O'Brian 2012). The effect of iron and ROS production on fungal colonization has indicated that the role of iron is more important for the establishment of necrotrophic pathogens than ectomycorrhizal fungal species.…”
Section: Discussionmentioning
confidence: 99%
“…Unsur Fe juga berperan dalam respons ketahanan tanaman terhadap infeksi penyakit (Greenshields et al 2014;Aznar et al 2015). Dong et al (2016) melaporkan bahwa ketersedian Fe yang tinggi mampu menurunkan perkecambahan dan pertumbuhan F. oxysporum, menurunkan produksi asam fusarik penyebab penyakit, dan pada akhirnya menurunkan keparahan penyakit pada tanaman pisang. Peran Fe dalam menekan suatu penyakit dapat terjadi melalui katalisasi pembentukan ROS (reactive oxygen species), peningkatkan ekspresi gen ketahanan PR1, deposisi kalose, akumulasi H 2 O 2 , peningkatan akumulasi p-coumaroylagmatine, dan aktivasi gen FER1 yang berperan dalam menjaga kesetabilan jumlah Fe dalam tanaman (Kieu et al 2012;Aznar et al 2015).…”
Section: Pembahasanunclassified
“…This increase in B content may be part of a defense mechanism of plants against Fusarium sp. for reducing or controlling disease severity (Dong et al 2016;Jiang et al 2016) and suggests a potentially important role for B in reducing disease development (Chappelka and Grulke 2016). Further studies should assess the role of B in stress and disease biology over time and for different experimental setups to confirm that its role in a stress-defense mechanism.…”
Section: Ecm Treatmentmentioning
confidence: 99%